(untitled) (The International Journal for Scientific Research, 2026)
This study aims to analyze the spatial change of urban expansion and vegetation cover in Al-Bukayriyah Governorate during the period (2015–2025), using Geographic Information Systems (GIS) and Remote Sensing techniques, in order to reveal the nature of transformations in land use and the interactive relationship between urban growth and vegetation cover change. The importance of the study comes within the framework of supporting the directions of Saudi Vision 2030 toward achieving sustainable urban development that preserves environmental resources and supports quality of life. The study relied on the descriptive analytical approach and the spatial analysis approach through processing Landsat 8 satellite imagery extracted via Google Earth Engine, with the employment of ArcGIS Pro software to conduct spatial analysis processes and produce thematic maps. NDVI and NDBI indices were also used to monitor changes in vegetation cover and urban expansion across different time periods. The results showed the existence of clear spatial changes in land uses, as the urban area increased from about (18.3 km²) in 2015 to (25.1 km²) in 2025, while the vegetation cover area decreased from (49.9 km²) to (23.3 km²) during the same period, with an annual loss rate estimated at about (2.6 km²/year). The results also showed the existence of a direct inverse relationship between urban expansion and vegetation cover, represented by the increase in NDBI values versus the decrease in NDVI values. The study also explained that vegetation cover is concentrated in the eastern sector of the governorate, while dry and semi-desert lands prevail in the western parts, reflecting the impact of natural variation and human activities in shaping the spatial patterns of land uses. The study demonstrated the possibility of employing Remote Sensing and GIS techniques in monitoring spatial changes with high accuracy and supporting spatial analysis and decision-making processes. The study concluded that Al-Bukayriyah Governorate witnessed clear spatial transformations during the study period between urban expansion and vegetation cover decline, with the continued semi-agricultural and semi-desert character of the governorate, which calls for strengthening sustainable planning policies and protecting environmental resources.